Порівняльна оцінка дії іонів і наночастинок міді й цинку на Pistia stratiotes (Araceae) за біохімічними показниками - Ольхович, О.П.; Кравченко, І.С.; Таран, Н.Ю.; Алексієнко, М.В. (Український ботанічний журнал, 2014)
Определено содержание пигментов, белка, идентифицированы и оценены количественно 17 аминокислот и 12 ацилкарнитинов у P. stratiotes под воздействием меди и цинка в ионной форме и коллоидных наночастиц, полученных диспергированием гранул металлов импульсами электрического тока в воде. Установлены достоверные изменения в содержании общего белка, отдельных аминокислот и ацилкарнитинов, свидетельствующие о нарушении белкового и липидного обменов. Выявлены различия воздействия ионов и наночастиц металлов. The content of pigments and proteins in P. stratiotes is determined. Seventeen amino acids and twelve acylcarnitines are identified and quantified under the action of copper and zinc in the ionic form and in the form of colloidal nanoparticles obtained by metal granules dispersing induced by electric current pulses in water. The significant changes in the content of total protein, individual amino acids and acylcarnitines indicate disruptions in protein and lipid metabolism. The differences in action of metal ions and nanoparticles were also detected.